Cereals and Pulses : Nutraceutical Properties and Health Benefits - Yu, Liangli; Tsao, Rong; Shahidi, Fereidoon, 1951- (Functional food science and technology series., 2012)
Cereals and Pulses: Nutraceutical Properties and Health Benefits provides a summary of current research findings related to phytochemical compositions and properties of cereal and pulse crops. Each major cereal and pulse is discussed for its nutraceutical properties. Coverage of cereals and pulse crops includes barley, oats, rice, rye, corn, adlay, wheat, buckwheat, psyllium, sorghum, millet, common beans, field peas, faba beans, chickpea, lentil and soybeans. Chapters for each crop discuss methods to improve crop utilization, nutraceutical components and properties, bioactive compositions, antioxidant properties, beneficial health effects, disease prevention activities and areas for future research. Also included are two chapters that discuss the beneficial health properties of dietary fibers and antioxidants with focus on the mechanisms involved in their biological actions. Edited and authored by an international team of respected researchers, Cereals and Pulses will serve as a timely and long lasting guide for scientists working in food ingredients, food product research and development, functional foods and nutraceuticals, crop breeding and genetics, post-harvest treatment and processing of cereal grains and pulses, and human nutrition to effect value-added food innovation for health promotion and disease risk reduction.